Natural Compounds as New Cancer Treatments - Barrajon, Enrique (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Cancer remains one of the main causes of morbidity and mortality worldwide. Although many pharmacological and clinical advances have been made, there is a constant need for new molecules to improve the overall options for treatment. Natural compounds from animal, microbial, vegetal, or fungal origin represent countless sources of new compounds that can be used as anticancer drugs, provided their activity, bioavailability, and toxicity are adequate. This book aims to compile both original articles and reviews that cover the most recent advances in the use of natural compounds for cancer treatment, and provide new objectives and advice for future research in the field of biological activity of natural compounds.